ADMINISTRATIVE SUPERVISION OF LOCAL SELF-GOVERNMENT IN THE BALTIC STATES: A COMPARATIVE VIEW - KIURIENÉ, VIOLETA (Journal of Education Culture and Society, 2020)
The article analyses models of administrative supervision of local self-government in the Baltic States (Latvia, Lithuania, Estonia) highlighting the advantages and disadvantages of these models. The research done in this article defines the theoretical concept of administrative supervision of local self-government; gives an overview of the legislative framework underpining the key administrative supervision bodies of local self-government in the Baltic States; discusses the issue of legal regulation and the present state of administrative supervision over local self-government units in the Baltic States; gives some theoretical and practical suggestions to develop this field in the Baltic States. The research methods employed in preparation of this article are theoretical methods of analysis of scientific literature and sources, legal acts and documents as well as comparative and logical analysis, induction and generalisation. Three Baltic States similar in their area, number of inhabitants, and governmental peculiarities have been chosen for the analysis.